2018
DOI: 10.1186/s12916-018-1208-2
|View full text |Cite
|
Sign up to set email alerts
|

Universal health coverage for refugees and migrants in the twenty-first century

Abstract: Migration is a determinant of health. Tackling the health needs of migrants and refugees will require action at the local, national, and global levels. Over the past 12 months, BMC Medicine has published a collection of articles under the title Migrant and Refugee Health (https://www.biomedcentral.com/collections/migrant-and-refugee-health) addressing a range of health issues affecting refugees and migrants in their countries of origin, on transit, and in their destination countries. In light of these articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…Inevitably, awareness about helpful mechanisms to access essential healthcare services differed between participants in FGDs. However, it is found that this had minimal impact on efficacy if participant contributions were correctly evaluated to understand what may help individuals to be proactive to improve their health [1,3,30]. The West Midlands, where this analysis was based, is a relatively poor region associated with low cost of living [11].…”
Section: Discussionmentioning
confidence: 99%
“…Inevitably, awareness about helpful mechanisms to access essential healthcare services differed between participants in FGDs. However, it is found that this had minimal impact on efficacy if participant contributions were correctly evaluated to understand what may help individuals to be proactive to improve their health [1,3,30]. The West Midlands, where this analysis was based, is a relatively poor region associated with low cost of living [11].…”
Section: Discussionmentioning
confidence: 99%
“…The world is going through an intense migration process; this population requires accessible and culturally appropriate health services. 22 A well-prepared armed forces may offer adequate response to health needs, including PS, acting in a complementary manner to the health sector. 23 The selection process is the basis of the PS, initiating the activities to provide an efficient management of medicines.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely viewed that maintaining adequate health conditions for the refugee is integral for their effective integration in society and the labour market (Campbell et al, 2014). Abubakar and Zumla (2018) showed that population movements inevitably cause adverse effects on health care delivery, increasing the responsibility of national governments and international bodies. Also, the United Nations' (UN) development of the Global Compact for Safe, Orderly and Regular Migration and the Global Compact on Refugees have increased the commitment to ensure high-quality care and curative health need of the refugee population.…”
Section: Introductionmentioning
confidence: 99%